Financial Ratio Analysis to Measure the Financial Performance of PT Adaro Energy Indonesia Tbk - Mariska Nur Hanifah; Muhammad Aras Prabowo; Muhammad Ashlyzan Razik; Mohd Rushdan Yasoa’; Nur Ain Ayunni Sabri (Trescode Green Organization, 2024)
This research aims to analyze financial ratios to assess the financial performance of PT Adaro Energy Indonesia Tbk during the 2020-2023 period. This research is a type of quantitative descriptive research using secondary data obtained from the official website of the Indonesia Stock Exchange (BEI) in the form of the Annual Financial Report of PT Adaro Energy Indonesia Tbk during the 2020-2023 period. The data collection technique used in this research is literature study. The results of financial ratio analysis show a generally positive company performance trend. The liquidity ratio increased, indicating the company's ability to meet short-term obligations. The solvency ratio decreased, indicating a reduction in dependence on debt. Activity ratios increased, reflecting effective asset management. The profitability ratio shows efficiency in generating profits from sales, although it still requires improvement in the aspects of return on investment and equity.